Fatigue life estimation of cylinder block using strain-life method - Nur Farah Bazilah, Wakhi Anuar (2009)
This project describes the fatigue life estimation of cylinder block using strain-life method. The main objectives of this project are to predict the fatigue life of the cylinder block using strain-life method and to identify the critical locations and to investigate the effect of loading. Aluminum alloys are selected as a cylinder block materials. The fatigue life predicted utilizing the finite element based fatigue analysis code. The structural model of the cylinder block was utilizing the solidworks. The finite element model and analysis were performed utilizing the finite element analysis code. In addition, the fatigue life was predicted using the strain-life approach subjected to variable amplitude loading. TET10 mesh and maximum principal stress were considered in the linear static stress analysis and the critical location was identifying at node (109730). From the fatigue analysis, Smith-Watson-Topper mean stress correction method was conservative life subjected to SAETRN loading. It is observed that the nitrided treatment and polished surface finish produce the longest life. Smith-Watson-Topper (SWT) mean stress correction is conservative method when subjected to SAETRN loading histories and the nitriding with polished combinations have been found the great influences on the fatigue life of cylinder block.